A Dynamic Discrete Dislocation Plasticity study of elastodynamic shielding of stationary cracks. (January 2017) - Gurrutxaga-Lerma, B.; Balint, D.S.; Dini, D.; Sutton, A.P.
Abstract: Employing Dynamic Discrete Dislocation Plasticity (D3P), an elastodynamic analysis of the shielding of a stationary crack tip by dislocations is studied. Dislocations are generated via Frank–Read sources, and make a negligible contribution to the shielding of the crack tip, whereas dislocations generated at the crack tip via homogeneous nucleation dominate the shielding. Their effect is found to be highly localised around the crack, leading to a magnification of the shielding when compared to time-independent, elastostatic predictions. The resulting attenuation of K I ( t ) is computed, and is found to be directly proportional to the applied load and to t .